Analisis Kesyariahan dalam Transaksi Penjualan pada Perusahaan Private equity dalam Perspektif Ekonomi Islam - Ai Ufi Lutfiatunnufus; MH Ainulyaqin; Kisanda Midisen; Sakum; Sukron Mamun (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study to analyze the relationship and similarities between the sales transaction process in a private equity manufacturing company and the concept of sales in the perspective of Islamic economics. The study was conducted at an automotive manufacturing company operating under a conventional economic system. The research method used is descriptive qualitative, employing literature review, participatory observation, in-depth interviews, and documentation. The findings indicate that there are similarities in transaction principles such as price agreements (akad), cost transparency, and made to order product manufacturing, which align with the akad istishna in Islamic. The study also highlights significant differences, particularly the implementation of penalty fees (riba) for late payments, which contradicts the Islamic prohibition of usury. This research recommends that companies consider integrating Islamic economic principles to improve business ethics and expand market opportunities, especially in the Syariah based industrial sector.